3x+32+(-24x)=6+-36x-6+-16x

Simple and best practice solution for 3x+32+(-24x)=6+-36x-6+-16x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+32+(-24x)=6+-36x-6+-16x equation:


Simplifying
3x + 32 + (-24x) = 6 + -36x + -6 + -16x

Reorder the terms:
32 + 3x + (-24x) = 6 + -36x + -6 + -16x

Combine like terms: 3x + (-24x) = -21x
32 + -21x = 6 + -36x + -6 + -16x

Reorder the terms:
32 + -21x = 6 + -6 + -36x + -16x

Combine like terms: 6 + -6 = 0
32 + -21x = 0 + -36x + -16x
32 + -21x = -36x + -16x

Combine like terms: -36x + -16x = -52x
32 + -21x = -52x

Solving
32 + -21x = -52x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '52x' to each side of the equation.
32 + -21x + 52x = -52x + 52x

Combine like terms: -21x + 52x = 31x
32 + 31x = -52x + 52x

Combine like terms: -52x + 52x = 0
32 + 31x = 0

Add '-32' to each side of the equation.
32 + -32 + 31x = 0 + -32

Combine like terms: 32 + -32 = 0
0 + 31x = 0 + -32
31x = 0 + -32

Combine like terms: 0 + -32 = -32
31x = -32

Divide each side by '31'.
x = -1.032258065

Simplifying
x = -1.032258065

See similar equations:

| 6(4x-y)+5= | | 14x+6x=20 | | 6x^3-13x^2+9x-2=0 | | 4x(2)=32 | | (5x-3)*(-2x-5)=0 | | (2x-3)(x)=54 | | 3a+2=a+8 | | [(8x+21)+(5x+63)]+2y=360 | | (8x+21)+(5x+63)+2y=360 | | 6(x+2)(x-4)= | | 8x+21=5x+63 | | (n+2)*8=24 | | (n-5)*5=10 | | 10x-9=101 | | 30+63+2x+7=180 | | x^2+7+1=0 | | 2(3a+b)-6(2a-3b)= | | (n+1)*9=27q | | (n-4)*6=12 | | 148-2x=25x+19 | | 7-9x=83-23x | | x*x+7x=12 | | a*8+6=3 | | 8(x+2)=4(x+10) | | 4x-5=72-7x | | 152-10x=9x+19 | | 8x+5=3x+0 | | 11x+30=2x+300 | | 230-3x=42+20 | | 6x-9=-33-8x | | -3xy*2xy= | | 79-4x=8x-19 |

Equations solver categories